Bilayered ZnTe/Cu1.4Te alloy thin films as a back contact for CdTe solar cells. (June 2019) - Du, Sheng; Zhu, Linyu; Li, Wei; Zhang, Jingquan; Wu, Lili; Wang, Wenwu
Highlights: ZnTe/Cu1.4 Te thin films were deposited by a three-source evaporation system. ZnTe/Cu1.4 Te bilayer structure was developed for CdTe solar cells. Significant enhanced performance was achieved for CdTe solar cells. Abstract: A low-resistance and stable back contact to p-type CdTe semiconductor is crucial for the high-efficiency CdTe solar cells. In this work, ZnTe/Cu1.4 Te bilayer alloys were fabricated by evaporation to form a new back-contact configuration for CdTe solar cells due to the well-matched interfacial property of ZnTe and the heavily p-doped property of Cu1.4 Te. The devices with single layer or double layers have an effective doping level from ∼5 × 10 13 to ∼3 × 10 14 cm −3, resulting in the improvement of device performance and apparent increase in quantum response in the CdS and CdTe regions, compared to the devices with only Au. Device performance demonstrates lower Schottky barrier and less carrier recombination for CdTe solar cells with ZnTe/Cu1.4 Te than that for the cells with Cu or Cu1.4 Te due to a better modification of the band structure. Time-resolved photoluminescence and dark capacitance-voltage measurements indicate the introduction of Cu or single Cu1.4 Te layer creates recombination centers to reduce the minority carrier lifetime from 100.9 to 78.7 ns and compensate net carrier concentration. The insertion of ZnTe buffer layers effectively prevents Cu diffusing to decrease recombination defects, resulting in longer minority carrier lifetime of 86.7 ns and higher carrier density, due to a well-matched interfacial property that is roughly 5% lattice mismatch at the CdTe/ZnTe interface. Finally, cell efficiency of >15%, open circuit voltage of >810 mV and fill factor of >73% for CdTe solar cells with an area of 0.24 cm 2 have been achieved. Accelerated aging tests show the stability of the cells over time is also improved by the incorporation of the ZnTe buffer layer.